Tranexamic acid use during total hip arthroplasty: A single center retrospective analysis. Issue 21 (May 2018) - Stoicea, Nicoleta; Moran, Kenneth; Mahmoud, Abdel-Rasoul; Glassman, Andrew; Ellis, Thomas; Ryan, John; Granger, Jeffrey; Joseph, Nicholas; Salon, Nathan; Ackermann, Wiebke; Rogers, Barbara; Niermeyer, Weston; et al.
Abstract: Background: Tranexamic acid (TXA) is an antifibrinolytic agent that has shown promise in reducing blood loss during total hip arthroplasty (THA). Several studies have reported side effects of high-dose TXA administration, including myocardial infarction (MI), thromboembolic events, and seizures. These possible side effects have prevented the widespread adoption of TXA in the surgical community. Methods: We conducted a retrospective chart review of 564 primary and revision THAs performed at a single academic center. Surgical patients received either no TXA or 1 g IV TXA at the beginning of surgery followed by a second bolus just before the surgical wound closure, at the surgeon's discretion. We analyzed differences in hemoglobin (Hb), hematocrit (Hct), estimated blood loss (EBL), and adverse events in patients receiving TXA versus patients not receiving TXA up to 2 days following surgery. Results: Significantly higher Hb and Hct values were found across all time points among patients undergoing primary posterior or revision THA who had received TXA. In addition, transfusion rates were significantly decreased in both primary posterior THAs and revision THAs when TXA was administered. Patients who received TXA experienced significantly fewer adverse events than those who did not for all surgery types. Conclusion: Administration of low-dose intravenous (IV) and intra-articular (IA) TXA does not appear to increase rates of adverse events and may be effective in minimizing blood loss, as reflected by Hb and Hct values following THA.